Prodigy. [2], The Icarus Society - Millar, Mark (Image Comics, 2023)
"Edison Crane is the world's smartest man...but what happens when he meets a criminal mastermind even smarter than he is and a secret society of geniuses who are using him for their own ends?"--Back cover.